2012
DOI: 10.1007/s10068-012-0046-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amylose content on cooking time and textural properties of white salted noodles

Abstract: White salted noodles were prepared from reconstituted flours of various amylose content to determine the effects of amylose content on noodle dough properties and texture of noodles cooked for optimum cooking time. With decrease of amylose content from 26.5 to 3.0%, optimum water absorption of noodle dough increased from 39 to 49% and cooking time of noodles decreased from 16 to 7 min. Hardness of cooked noodles prepared from reconstituted flour consistently decreased with increase in proportion of waxy starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
(28 reference statements)
2
14
0
Order By: Relevance
“…The changes in noodle texture are in agreement with previous correlation analyses between amylose content and noodle eating qualities, including hardness, cohesiveness, and springiness (Heo, Baik, Kang, Choo, & Park, 2012;Kaur et al, 2016). Starch functionality in the food environment can be predicted using starch characterization techniques; Li, Dhital, Slade, et al (2019) showed that starch swelling and interactions between swollen granules of HAW were greatly reduced at amylose levels higher than 50%, consistent with the observation of cooked HAW noodle under CSLM (Fig.…”
Section: Protein-starch Matrix Affects Haw Noodle Propertiessupporting
confidence: 89%
“…The changes in noodle texture are in agreement with previous correlation analyses between amylose content and noodle eating qualities, including hardness, cohesiveness, and springiness (Heo, Baik, Kang, Choo, & Park, 2012;Kaur et al, 2016). Starch functionality in the food environment can be predicted using starch characterization techniques; Li, Dhital, Slade, et al (2019) showed that starch swelling and interactions between swollen granules of HAW were greatly reduced at amylose levels higher than 50%, consistent with the observation of cooked HAW noodle under CSLM (Fig.…”
Section: Protein-starch Matrix Affects Haw Noodle Propertiessupporting
confidence: 89%
“…Cooking time (CT) was determined according to the method of Heo et al (2012) with some modifications. Noodles (20 g, 200 mm long) were put into boiling water (200 ml, 98~100°C), and then took out a noodle every 20s.…”
Section: Cooking Time (Ct)mentioning
confidence: 99%
“…A texture analyzer is a widely used instrument for objectively evaluating the noodles' edible quality (Li, Dhital, & Wei, 2017). It can evaluate the hardness, elasticity, adhesion, and tensile strength of cooked noodles with good reproducibility (Heo, Baik, Kang, Choo, & Park, 2012). Chen et al (2002) evaluated the adhesion, extensibility, and chewiness of wheat flour noodles mixed with potato starch by using a texture analyzer, and they established the correlation between the starch noodle quality and gel properties of original starches.…”
mentioning
confidence: 99%